Wireless access policy for electronic communications services (WAPECS): Collision between theory and practice. Issue 8 (August 2016) - El-Moghazi, Mohamed; Whalley, Jason; Irvine, James
Abstract: One of the first practical implementations of flexible radio spectrum property rights was initiated in Europe in 2005 under the name 'Wireless Access Policy for Electronic Communication Services (WAPECS)'. WAPECS aimed to introduce more flexibility into the European spectrum management framework by allowing technology and service neutrality. Internationally, the European Conference of Postal and Telecommunications Administrations (CEPT) have been keen to introduce more flexibility into the international service allocation framework. One of the main findings of this paper is the identification of different negative perceptions and disagreement about WAPECS among industry and regulatory stakeholders. Moreover, it is shown that concerns over WAPECS include that the flexibility associated with it may contradict with spectrum use efficiency and that the responsibility of resolving interference issues moves from the regulator to operators. The assessment of the influence of WAPECS on the market shows that while the concept was aimed mainly towards removing the spectrum usage restriction for industry, they have not appreciated this mainly due to the high cost and uncertainty associated with flexibility. On the other hand, several positive impacts of WAPECS are revealed including removing technology designation from CEPT decisions. The paper shows also that the international Radio Regulations (RR) can, to a certain extent, accommodate WAPECS. Highlights: The development of WAPECS was driven by the European Commission and a few European countries. WAPECS may contradict the efficient use of spectrum. The telecommunications industry did not like the high costs and uncertainty associated with WAPECS. WAPECS has had a positive impact of removing technology designations from CEPT decisions. International Radio Regulations can only accommodate WAPECS to a certain extent.